LAS INTERACCIONES ENTRE LOS PAÍSES DEL AFTA Y DE LA APEC Y SUS INFLUENCIAS EN LA REGIÓN - Daquila, Teófilo C. (1997)
It attempts to trace and identify the divergences of ASEAN and APEC member countries with respect to the three areas of work agreed upon by ABPEC at the 1993 Seattle Summit: trade liberalization, trade facilitation and economic cooperation; differences that are explained, among other reasons, buy the different degrees of economic development achieved, different industrialization policies and different tariff structures. It is concluded that, within ASEAN, member countries differ in the speed of the trade liberalization process and in the allocation of industrial projects in the pursuit of industrial cooperation. Within APEC, countries have different points of view and interact differently in terms of focus, timelines, trade blockade issues, and open regionalism. But in both cases, countries converge on the need to achieve liberalization and openness to trade and investment.